Natural environment accessibility through green architecture in Malaysian low-cost housing development from Islamic principles / Azlan Ariff Ali Ariff ... [et al.] - Ali Ariff, Azlan Ariff; Ismi, Mohamad Faris; Mohd Tajul Hasnan, Mohd Tajul Izrin; Wan Mahadi, Wan Mohammad Zaeim; Azmy, Mohd Syafiq; Ramli, Siti Aishah; Alias, Nur Ulfah Awatif Umairah (UiTM Press, 2024)
Rapid urbanisation has led to an urgent need to enhance the quality of life in urban environments. The development of low-cost housing, often without sustainable design, has disconnected urban residents from nature, affecting the low-income population. This disconnection has increased over the past few decades, restricting natural human tendencies and reducing rights to a healthy living environment. To reconnect residents with nature and improve urban living conditions, low-cost housing developments should consider incorporating sustainable design and green architecture strengthened by respect to Islamic values as the significant element of Malaysian identity. The purpose of this paper is to emphasise the importance of accessibility to nature by highlighting a more comprehensive understanding of the significance of natural environment accessibility from the Islamic principles, particularly in low-cost housing development areas that have been planned with poorly built environments. The concept of biophilia which postulated that people have innate tendencies towards the natural environment poses an important foundation for green architecture approaches which later can be developed into a series of green building regulations and rating tools. In this study, these green rating tools are utilised to evaluate the significance of natural environment accessibility for developing low-cost housing through comparative analysis. From the literature review, comparative analysis and case study, it is found that the accessibility to the natural environment needs to be improved significantly in the low-cost housing project through involvement of various parties in built environment practices. By considering the Islamic viewpoint, which advocates for human roles in the preservation and conservation of natural environments, the purpose of this paper is to bring attention to the significance of aligning the translation of biophilic theory in green architecture through natural environment accessibility in low-cost housing in respect to Islamic values, upholding Malaysian identity as Islamic country.